Scratch as an Environment for Learning the Coordinate System by Elementary School Students - Ahlam Anabousy; Wajeeh Daher; Ronit Bassan-Cincinatus (MDPI AG, 2023)
The focal point of mathematics education research is to comprehend how students develop and consolidate their abstract mathematical knowledge. As goal of this research, the focus was on exploring the processes that sixth-grade students used to construct mathematical concepts linked to the coordinate system. In this study, a group of eight students was selected for research purposes. Video recordings were used to collect data through observations. The Abstraction in Context (AiC) framework was utilized to analyze the students' processes that took place within the Scratch environment. The research findings suggested that the grade six students successfully constructed most of the anticipated knowledge components, consolidated their previous knowledge related to the zero concept, and began to develop new ones. Specifically, the students were able to construct the concept of zero as a number that is neither positive nor negative, as well as comprehend the X and Y axes.